P-adaptive neuro-fuzzy and pd-fuzzy controller design for position control of a modified single acting pneumatic cylinder - Azman, M. Asyraf (2013)
Pneumatic systems are widely used in the automation industry and in the field of automatic control. This work proposes two control approaches, Proportional Adaptive Neuro-Fuzzy (P-ANFIS) controller and PD-Fuzzy (PDFLC) controller for a modified single acting pneumatic cylinder position control. The design steps of each controller implemented on MATLAB/Simulink are presented. A model based on position system identification is used for the controller design. Then, the simulation results are analyzed and compared to illustrate the performance of the proposed controllers. Finally, the controllers are tested with the real plant in realtime experiment to validate the results obtained by simulation. Results show that P-ANFIS controller offer better control compared to PDFLC.